Quantitative separation of radioactive sterols and bile acids in human faeces - Lewis, B. (1965)
A method is described for the quantitative separation of radioactive bile acids and neutral sterols in human faeces on a potassium hydroxide-treated silicic acid column. Results obtained with faecal extracts containing metabolites derived from radioactive cholesterol, cholic acid, and chenodeoxycholic acid show that the efficiency of extraction is at least 96% and that mutual contamination between the bile-acid and sterol fractions is between 0·7 and 3·8%. The method gives better results than one based on separation of the faecal steroids into saponifiable and unsaponifiable material.